Dinamika Interaksi Sosial Lintas Agama: Persepsi dan Perilaku Toleransi Beragama di Perguruan Tinggi - Noor Ainah; M. Zulkifli; Muhammad Hasan Said Iderus (Indonesian Journal of Islamic Religious Education, 2025)
This research investigates the dynamics of interfaith social interactions in the campus environment. Focused on students perceptions and behaviors regarding religious tolerance, Indonesia, as a country with many religions and beliefs, needs a deep understanding of how the younger generation, especially students, build and manage social relationships with people from different religious backgrounds. This research yielded several important findings using qualitative research methods on 200 students and in-depth interviews with 10 informants from various religious backgrounds. The research results show that 75% of respondents have positive social interactions with friends of different religions, but 25% still feel uncomfortable in certain situations. Family background and education, the intensity of interfaith interactions, understanding of tolerance principles, and the social climate on campus are some components that influence interaction dynamics. Furthermore, this study found that students who have had early experiences